Does postgraduate year training program for dentists worsen the imbalance of geographical distribution of dentists in Taiwan? - Feng-Chou Cheng (Journal of Dental Sciences, 2020)
Background/purpose: Taiwan implemented the non-compulsory postgraduate year training program for dentists (PGYD) in 2010. Previous studies found that training institutions for dentists are mostly distributed in metropolitan areas. This study explored whether the PGYD system might worsen the imbalance of geographical distribution of dentists in Taiwan. Materials and methods: This study collected the data of population, the number of practicing dentists from 2010 to 2018, and the number of practicing dentists in the training institutions in 2018 to draw the Lorenz curve and to calculate the Gini coefficient for evaluating whether the PGYD system might worsen the imbalance of geographical distribution of dentists in Taiwan. Results: Our results showed that the uneven geographical distribution of overall practicing dentists did not deteriorate after the implementation of the PGYD system. However, the uneven geographical distribution of practicing dentists in training institutions was more serious than the uneven geographical distribution of overall practicing dentists. Conclusion: Because the PGYD system is not mandatory, dentists engage in training program and select training institutions as driven by the market factors. After completion of the PGYD training, dentists choose the practice location as driven by the market factors again and this in turn redistributes the dentists to different regions of Taiwan. In addition, major dentist policies may also result in the movement of dentists to various regions of Taiwan. Thus, the market-driven redistribution of dentists to different regions of Taiwan finally reduces the imbalance of geographical distribution of dentists in Taiwan caused by the PGYD system.